Diverse regional sustainability strategies: template for the future or squandered resources?. (1st January 2012) - Harper, Gavin; Wells, Peter
To date, regional sustainability has been given attention because it is often the case that key actors and stakeholders can be coordinated at this level. However, scant attention has been given to the question of whether and to what extent regionally-defined solutions for sustainability could and should be different to each other. Taking the example of the automotive industry this paper explores both theoretically and empirically the extent of diversity at a regional level in the UK where three regions (the North East, the West Midlands, and Wales) have adopted quite distinct trajectories and emphases (electric cars, low carbon cars and hydrogen cars, respectively) around novel mobility infrastructures and their attendant industrial bases. We use the transitions framework to interrogate the degree to which diversity is an inevitable outcome from the quest for sustainability at the local and regional levels considered against a backdrop of turbulent change as regional development agencies are abolished in favour of local enterprise partnerships.